The Effectiveness of Mathematics 2.0 Learning through Digital Educational Games in Stimulating Early Childhood Mathematical Abilities - Lismayani, Angri; Pratama, Muhammad Isbar (EduLine: Journal of Education and Learning Innovation, 2025)
Mathematics 2.0 is a combination of mathematics and technology, which is essential due to the significant role mathematics plays in advancing technology, science, and education. This study aims to examine the effectiveness of Mathematics 2.0 learning through digital educational games in stimulating early childhood mathematical abilities. A mixed-methods approach was employed, utilizing qualitative methods to illustrate the importance of mathematics learning through educational games for young children, and quantitative methods to measure the impact of such games on stimulating early mathematical skills. The sample consisted of 30 early childhood students, with data collected through interviews and observations. The results of the study indicate that educational games such as Lumio and ScratchJr have a significant effect in stimulating mathematical abilities in early childhood.